RURAL TOURISM IMPACT ON THE LIFE QUALITY OF THE LOCAL COMMUNITY: A CASE STUDY OF WESTERN SERBIA - Panić, Aleksa; Vujko, Aleksandra; Knežević, Miroslav (Economics of Agriculture, 2024)
This study analyzes the impact of rural tourism on the quality of life in Western Serbia, focusing on four tourist villages: Koštunići, Vraneša, Sunčana reka, and Sirogojno. Utilizing a mixed-methods approach with 469 respondents, we assessed local perceptions of economic, social, and environmental influences resulting from tourism development. The Likert scale revealed positive economic effects, significant shifts in social conditions and thinking, and concerns about environmental degradation. The study underscores rural tourism’s multifaceted nature, emphasizing positive economic impacts, socio-cultural improvements, and environmental considerations. The conclusions highlight the need for responsible, sustainable practices to optimize benefits while mitigating negative consequences. Recommendations include addressing gender disparities and prioritizing environmental concerns in future rural tourism development. This research contributes to understanding rural tourism’s implications, offering insights for policymakers, local communities, and practitioners striving for balanced, prosperous, and sustainable rural development in Western Serbia and beyond.